Perancangan Aplikasi Kompresi File Video Dengan Menggunakan Algoritma Start Step Stop Code - Joni Alpensius Simatupang; Guidio L. Ginting; Fince Tinus Waruwu (Forum Kerja Sama Penddikan Tinggi (FKPT), 2022)
Video files have a large size that affects the storage space and the delivery process. This size is a factor in how much storage space will be used and how long it will take to send files. The longer the video file, the larger the size can be overcome by doing the compression process. Compression is done to reduce the size of a file. The compression algorithm that can be used is the start step stop code algorithm. The advantage of the start step stop code algorithm is that it first determines the value of n = 0, then determines the value of a = start + nx stop, then the subset starting with n will be preceded by the number '1' and followed by the insertion of '0' followed by a combination of bits. a.